NMDA Receptor-Dependent Metaplasticity by High-Frequency Magnetic Stimulation - Tursonjan Tokay; Timo Kirschstein; Marco Rohde; Volker Zschorlich; Rüdiger Köhling (Neural Plasticity)
High-frequency magnetic stimulation (HFMS) can elicit N-methyl-D-aspartate (NMDA) receptor-dependent long-term potentiation (LTP) at Schaffer collateral-CA1 pyramidal cell synapses. Here, we investigated the priming effect of HFMS on the subsequent magnitude of electrically induced LTP in the CA1 region of rat hippocampal slices using field excitatory postsynaptic potential (fEPSP) recordings. In control slices, electrical high-frequency conditioning stimulation (CS) could reliably induce LTP. In contrast, the same CS protocol resulted in long-term depression when HFMS was delivered to the slice 30 min prior to the electrical stimulation. HFMS-priming was diminished when applied in the presence of the metabotropic glutamate receptor antagonists (RS)-α-methylserine-O-phosphate (MSOP) and (RS)-α-methyl-4-carboxyphenylglycine (MCPG). Moreover, when HFMS was delivered in the presence of the NMDA receptor-antagonist D-2-amino-5-phosphonovalerate (50 µM), CS-induced electrical LTP was again as high as under control conditions in slices without priming. These results demonstrate that HFMS significantly reduced the propensity of subsequent electrical LTP and show that both metabotropic glutamate and NMDA receptor activation were involved in this form of HFMS-induced metaplasticity.